2003
DOI: 10.1213/01.ane.0000090320.46129.be
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Interscalene Block for Elective Shoulder Surgery: Loss of Benefit over Early Postoperative Block After Patient Discharge to Home

Abstract: Preoperative interscalene block with levobupivacaine provides safe and effective analgesia for same-day elective shoulder surgery, but the benefit of this one-time intervention does not persist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…First, Wurm et al showed no differences in SF-36 outcomes at 1 and 7 days postoperatively, but this study did not describe its basis of sample size determination (interscalene block performed preoperatively versus postoperatively, n=102) 13. In a more recent study, no SF-36 differences were seen at 12 weeks postoperatively when comparing spinal anesthesia and GA for vaginal hysterectomy 14…”
Section: Discussionmentioning
confidence: 82%
“…First, Wurm et al showed no differences in SF-36 outcomes at 1 and 7 days postoperatively, but this study did not describe its basis of sample size determination (interscalene block performed preoperatively versus postoperatively, n=102) 13. In a more recent study, no SF-36 differences were seen at 12 weeks postoperatively when comparing spinal anesthesia and GA for vaginal hysterectomy 14…”
Section: Discussionmentioning
confidence: 82%
“…Rebound pain as well as incomplete effects, such as partial block or failure of the nerve block, have been reported to occur. 1,2,7,28 Furthermore, most patients who receive rotator cuff surgery are older, so we should consider the safety of the interscalene block in this age group with pulmonary comorbidity. All the successful interscalene blocks could affect the phrenic nerve, and this might lead to respiratory distress or diaphragmatic paresis.…”
Section: Discussionmentioning
confidence: 99%
“…However, this technique has been associated with potential side effects and complications, such as rebound pain, phrenic nerve palsy respiratory distress, or diaphragmatic paresis. [12][13][14] The combination of SSNB and ANB has been also used effectively for anesthesia in shoulder arthroscopy and these blocks have provided safe analgesia in intraoperative and early postoperative periods. 6 The philosophy of regional nerve blocks is that the local anesthetic should be infiltrated close to the nerve to the maximum extent.…”
Section: Discussionmentioning
confidence: 99%